Podoby profesní spolupráce ve škole případové studie - Švec, Vlastimil; Baranová, Petra; Dvořáková, Tereza 1977-; Ďulíková, Lenka; Egerle, Jan; Janík, Tomáš 1977-; Márová, Ivana; Paroubková, Alena; Veselá, Valentýna (Masarykova univerzita, 2022)
Title in English: Interprofessional collaboration in school: a collection of case studies The book provides an introduction in the field of (inter)professional collaboration in school. It offers theoretical background for interprofessional collaboration and on the basis of case studies it illustrates its' various forms within school education. The book could serve as source in preparation and development in helping professions.
Keywords: interprofessional collaboration; pedagogical professions; helping professions; school; school education